Changes of B and T lymphocytes and selected apopotosis markers in Hashimoto's thyroiditis. Issue 7 (17th January 2011) - Kaczmarek, Elzbieta; Lacka, Katarzyna; Jarmolowska-Jurczyszyn, Donata; Sidor, Anna; Majewski, Przemyslaw
Abstract : The aim was to assess changes of B and T lymphocytes and selected apoptotic markers in Hashimoto thyroiditis (HT) cases on the basis of quantitative immunohistochemical studies (CD20, CD43, CD8, Bcl-2, caspase-3). The control group comprised colloid goitres without inflammatory infiltrate taken from 10 female patients. Thyroid specimens were obtained retrospectively from 40 patients. The immunohistochemical reactions were subject to quantitative evaluation performed using image-processing methods, including a spatial visualisation of the markers' expression. The percentage of Bcl-2 reactions in HT (mean 3.65%, SD 2.94%) was significantly lower than in the control group (mean 13.99%, SD 5.04%), while the thyroid follicles in HT samples exhibited a higher degree of staining for caspase-3 (mean 1.10%, SD 1.03%) in contrast to normal control tissues (mean 0.48%, SD 1.02%). The results from this study indicate that apoptosis plays a major role in the patogenesis of autoimmune thyroid diseases containing the main pathogenic events in the lesion of thyroid follicular cells in HT. Moreover, the reactivity of CD43 and CD20 was significantly higher in Hashimoto disease, while CD8 was not significantly different from the control group.